Effects of drinking slightly acidic electrolyzed water on the growth health, blood physiology, and intestinal development in mice - Zhifang Shi; Lei Xi; ShuiLin Gao; ZhengYang Shi; XiaoTong Wang; Zhangying Ye; Pu Cheng (Scientific Reports)
Abstract Slightly acidic electrolyzed water (SAEW) as a disinfectant might be ingested by humans and animals along with food and drinking water. The present study explored whether adding SAEW to drinking water affects the drinking water intake, food intake, body weight, intestinal morphology, digestive enzyme activity, and antioxidant enzyme activity of mice. This will provide a theoretical basis for the biosafety of SAEW as a food and drinking water disinfectant. The present study selected and randomly divided 96 4-week-old Kunming mice into three groups: control, 0.5 mg/L SAEW, and 5.0 mg/L SAEW groups. The experiment lasted 60 days. The present study showed that drinking SAEW had no noticeable effect on the food intake, water intake, body weight, and blood biochemical indexes of mice. SAEW significantly increased the plasma superoxide dismutase inhibition rate, glutathione content, and total antioxidant capacity of mice (p < 0.05). The fructose-6-phosphate kinase, isocitrate dehydrogenase, and malate dehydrogenase activities of mice in the SAEW group were significantly increased. Furthermore, SAEW promoted the morphological development of the small intestine and increased the activities of amylase, lipase, and protease. Therefore, the 0.5 and 5.0 mg/L SAEW was beneficial for mice, and improved the body’s antioxidative, glucose-metabolizing, and digestive ability.